THE ROLE OF GOOD CORPORATE GOVERNANCE MODERATION IN SUSTAINABILITY, ACCOUNTING CONSERVATISM, AND EARNINGS MANAGEMENT: AN EMPIRICAL STUDY ON INDONESIAN PUBLIC COMPANIES - Deddy Kurniawansyah; Muhammad Dzakwan Ihza Mahendra; Iswajuni (UPT Publikasi Ilmiah UNISBA, 2025)
This study aimed to examine the influence of sustainability report and accounting conservatism on earnings management, and the moderating role of good corporate governance on the effect of sustainability report and accounting conservatism on earnings management. The population of this study was the entire company sector listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique for this study was the census method that amounted to 260 annual reports and sustainability reports. The data analysis technique used PLS-SEM with the help of SmartPLS 3.0 software. The results of this study show that sustainability report and accounting conservatism had a positive effect on earnings management. Good corporate governance did not strengthen the positive relationship between sustainability report and accounting conservatism on earnings management of the entire company in 2018-2022.